Impact of Covid on Instructor Well-being Within ‘Studio’ Based Design and Construction Teaching - McMeel, D; Petrovic, EK; Potangaroa, R; Jadresin-Milic, R (European Council for Computing in Construction, 2025)
Studio-based pedagogy, integral to design and construction education, emphasizes hands-on exploration, collaboration, and face-to-face interactions. The COVID-19 pandemic disrupted this model, shifting learning online and exacerbating workloads, pedagogical challenges, and community-building issues. This study investigates these effects through a survey of New Zealand educators, analyzed using inductive thematic methods. Findings highlight significant stress from tensions between traditional and online models, underscoring the urgent need for improved digital literacy, redesigned learning environments, and enhanced online community-building strategies. This research contributes insights into adapting studio-based pedagogy for resilient and effective online education.